Beyond the Postcolonial - Varughese, E. Dawson. author. aut Link
XI, 239 p.
Keywords: With the backdrop of new global powers, this volume interrogates the state of writing in English. Strongly interdisciplinary, it challenges the prevailing orthodoxy of postcolonial literary theory. An insistence on fieldwork and linguistics makes this book scene-changing in its approach to understanding and reading emerging literature in English.